2017
DOI: 10.1111/ppl.12653
|View full text |Cite
|
Sign up to set email alerts
|

Diffusional conductance to CO2 is the key limitation to photosynthesis in salt‐stressed leaves of rice (Oryza sativa)

Abstract: Salinity significantly limits leaf photosynthesis but the factors causing the limitation in salt-stressed leaves remain unclear. In the present work, photosynthetic and biochemical traits were investigated in four rice genotypes under two NaCl concentration (0 and 150 mM) to assess the stomatal, mesophyll and biochemical contributions to reduced photosynthetic rate (A) in salt-stressed leaves. Our results indicated that salinity led to a decrease in A, leaf osmotic potential, electron transport rate and CO con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(19 citation statements)
references
References 59 publications
(115 reference statements)
1
18
0
Order By: Relevance
“…The regulation of stomata has been described as a process linked to transport and absorption of nutrients (Aranjuelo et al., 2014). This strategy has been reported under abiotic stresses such as salinity (Wang et al., 2017) or high temperature (Aranjuelo et al., 2006; Jauregui et al., 2015), among other factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The regulation of stomata has been described as a process linked to transport and absorption of nutrients (Aranjuelo et al., 2014). This strategy has been reported under abiotic stresses such as salinity (Wang et al., 2017) or high temperature (Aranjuelo et al., 2006; Jauregui et al., 2015), among other factors.…”
Section: Discussionmentioning
confidence: 99%
“…This process is greatly affected by ammonium nutrition in wheat plants. In parallel with other compounds that impair photosynthetic machinery via stomatal regulation (Aranjuelo et al., 2014) or to the “avoidance mechanism” under saline stress (Wang et al., 2017), ammonium-fertilized plants are able to regulate their stomatal function and thus prevent further ammonium accumulation in leaves via the transpiratory stream, which otherwise could be extremely harmful to cell functions. The counterbalance for the plant is that stomatal closure restricts the entrance of CO 2 , with negative consequences for photosynthesis and biomass productivity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, A was also tightly correlated with V cmax and J max , which supports a biochemical limitation in photosynthesis. In fact, previous studies suggested that the major photosynthetic limiting factors in C 3 plant leaves are modified by slight changes in the growing conditions ( Yamori et al , 2011 ; Wang et al , 2018 ). Therefore, the LES trait trade-offs may relate to the photosynthetic limitations, shifting the cause to leaf anatomy and/or biochemical changes.…”
Section: Discussionmentioning
confidence: 99%
“…A photosynthetic limitation analysis is a helpful tool to quantify the relative limitation of g s , g m , and the photosynthetic biochemistry on A ( Grassi & Magnani, 2005 ; Buckley & Diaz-Espejo, 2015 ), and it has been widely used recently, especially under stress conditions ( Flexas et al , 2009 ; Galle et al , 2009 ; Tosens et al , 2016 ; Wang et al , 2018 ). In this study, the photosynthetic limitations, including the relative stomatal ( l s ), mesophyll ( l m ), and biochemical ( l b ) limitations at different N a , were calculated using fitted A , g s , g m , and V cmax values according to Grassi and Magnani (2005) :…”
Section: Methodsmentioning
confidence: 99%
“…In C 3 plants, the light-saturated leaf photosynthetic rate ( A ) is limited by stomatal conductance ( g s ), mesophyll conductance to CO 2 ( g m ), and/or the photosynthetic biochemistry related to either carboxylation velocity, V cmax , or the maximum electron transport rate set by photochemical and Calvin cycle activities, J max ( Tosens et al , 2012 ; Tomás et al , 2013 ; Tosens et al , 2016 ; Veromann-Jürgenson et al , 2017 ). Grassi and Magnani (2005) developed a method to estimate the partial contribution of each limiting factor to the overall reduction of photosynthesis; this approach has since been applied to many species under a variety of environmental stresses ( Flexas et al , 2009 ; Galle et al , 2009 ; Galle et al , 2011 ; Galmés et al , 2013 ; Wang et al , 2018 ). Although the limiting effects of g s , g m , and photosynthetic biochemistry on A are dependent on the species, A has been suggested to be first inhibited by a decrease in g s and g m under drought conditions, with the biochemical inhibition occurring later, under more severe drought stress conditions ( Grassi & Magnani, 2005 ; Flexas et al , 2009 ; Galle et al , 2009 ; Galle et al , 2011 ; Galmés et al , 2013 ; Galmés et al , 2017 ).…”
Section: Introductionmentioning
confidence: 99%